The moral dilemma of high stakes gambling in Native communities - Little, Margo, 1947- (Laurentian University, 1997)
In Canada today, Native people grapple with an increasingly bleak economy. According to Statistics Canada, only forty-three per cent of Aboriginal people have jobs; whereas, the employment average for other Canadians is sixty-one per cent. The Canadian average annual income is $24,876 but Native Canadians receive $16,560 per annum. Eight per cent of mainstream Canadians receive social assistance; twenty-nine per cent of Natives do (Fisher 16). This perpetual marginalization has spurred many First Nations communities to pursue commercial gaming as a source of economic salvation. In this paper I will examine the legacy of gambling in Native culture and the ethical dilemmas facing bands who attempt to use gaming operations as a solution to economic ills.